All-cause mortality risk in elderly individuals with disabilities: a retrospective observational study. Issue 9 (13th September 2016) - Wu, Li-Wei; Chen, Wei-Liang; Peng, Tao-Chun; Chiang, Sheng-Ta; Yang, Hui-Fang; Sun, Yu-Shan; Chan, James Yi-Hsin; Kao, Tung-Wei
Abstract : Objectives: Disability is considered an important issue that affects the elderly population. This study aimed to explore the relationship between disability and all-cause mortality in US elderly individuals. Design: Retrospective and longitudinal designs. Setting: Data from the National Health and Nutrition Examination Survey (NHANES 1999–2002) conducted by the National Center for Health Statistics of the Centers for Disease Control and Prevention. Participants: A total of 1834 participants in the age range 60–84 years from NHANES 1999–2002. Main outcome measures: We acquired five major domains of disability (activities of daily living (ADL), general physical activities (GPA), instrumental ADL (IADL), lower extremity mobility (LEM) and leisure and social activities (LSA)) through self-reporting. We applied an extended-model approach with Cox (proportional hazards) regression analysis to investigate the relationship between different features of disability and all-cause mortality risk in the study population. Results: During a mean follow-up of 5.7 years, 77 deaths occurred. An increased risk of all-cause mortality was identified in elderly individuals with disability after adjustment for potential confounders (HR 2.23; 95% CI 1.29 to 3.85; p=0.004). Participants with more than one domain of disability were associated with a higher risk of mortality (ptrend =0.047). Adjusted HRs and 95% CIs for each domain of disability were 2.53 (1.49 to 4.31), 1.99 (0.93 to 4.29), 1.74 (0.72 to 4.16), 1.57 (0.76 to 3.27) and 1.52 (0.93 to 2.48) for LEM, LSA, ADL, IADL and GPA, respectively. Conclusions: The results of this study support an increased association between disability and all-cause mortality in the elderly in the USA. Disability in LEM may be a good predictor of high risk of all-cause mortality in elderly subjects.